Superior mesenteric artery syndrome in an adolescent with anorexia nervosa during the COVID-19 pandemic. A clinical case report - Huete Cordova, Maria (2021)
The case of an adolescent patient diagnosed with Superior Mesenteric Artery Syndrome caused by emaciation resulting from an eating disorder (Anorexia Nervosa, AN) es described. Its clinical course was severely accentuated by the COVID-19 pandemic. The Syndrome is due to the compression of the third portion of the duodenum between the superior mesenteric artery and the aorta. The main clinical, etiopathogenic and diagnostic characteristics of AN are described; its early diagnosis is essential to improve a prognosis complicated by the consequences of weight loss and malnutrition. Anxious and depressive comorbidities associated with the stress caused by the confinement, and the patient’s obsessive personality traits required a joint treatment by the Pediatry and Child and Adolescent Psychiatry Services, the latter with individual and family psychotherapy interventions.